2度の気道緊急を呈した喉頭魚骨異物例(Larynx fish bone foreign bodies that caused airway obstruction twice). Issue 3 (March 2015) - (Eri Uemura), 上村 恵理; (Daisuke Mizu), 水 大介; (Takahiro Atsumi), 渥美 生弘; (Koichi Ariyoshi), 有吉 孝一
ABSTRACT: Fish bone foreign bodies are often seen in the emergency department, but rarely cause airway obstruction. We describe the case of laryngeal fish bone foreign bodies that caused airway obstruction twice. A 20–month–old boy presented stridor after dinner, he was diagnosed with a fish bone foreign body in the glottis by laryngoscopy. We removed it under general anesthesia. After the removal, we confirmed the absence of foreign bodies using a laryngoscope. He was discharged the day after removal, but 6 days after discharge, he presented stridor and salivation appeared again. We performed laryngoscopy and found a subglottic foreign body. We performed tracheotomy and removed the foreign body. Subglottic foreign bodies are rare, but can cause airway obstruction. Laryngoscopy is insufficient to confirm the absence of subglottic foreign bodies, so we should consider bronchoscopy for this purpose.